Mysterious air pollution in south China linked to volcanic emissions from the Philippines - Changqing Lin; Jian Zhen Yu; Eddie Lee; Pak-Wai Chan; Jackie Wai-Yin Ng; Ying-Wa Chan; Tianshu Zhang; Yiang Chen; Hanzhe Chen; Zijing Zhang; Samuel Ho-Kwong Chui; Jimmy C. H. Fung; et al. (Communications Earth & Environment)
Abstract A mysterious air pollution event occurred in south China on April 1–2, 2024, despite the prevailing southerly airflow that is typically associated with clean air. Here, we identified the source of this event using a multi-scale data system that combines large-scale monitoring and modeling data with advanced measurements of aerosol chemical compositions in Hong Kong. Large-scale satellite measurements and chemical transport modeling detected the transboundary transport of a volcanic plume originating from the Taal volcano in the Philippines. Unusually high levels of sulfate (reaching 75% of fine particulate matter) and phosphorus (up to 93 ng/m³) in Hong Kong supported this finding. These analyses prompted the development of a real-time chemical-wind index to identify the occurrence of air pollution associated with volcanic emissions. Our results highlight the value of integrating multi-scale real-time data capabilities to promptly attribute air pollution events to their sources and protect at-risk populations.